Bioactivity of black cumin oil on the senescence of HER-2-overexpressing breast cancer cells - Faradiba Nur Ahlina,; Lisyaratih Anggriani,; Irfani Aura Salsabila,; Riris Istighfari Jenie, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Senescence-induced therapy has been improved to increase its cytotoxicity and reduce the resistance of breast cancer cells to chemotherapy agents. An example of a potential senescence-inducing agent is black cumin oil (BCO) because one of its major compounds, α-pinene, can induce senescent cells. This study aims to explore the senescence-inducing activity of BCO in HER2-overexpressing breast cancer cells (MCF7/HER2). The yield obtained from hydro-distillation of BCO was 0.54%, and the main compounds were p-cymene (48.03%), dihydrocarveol (11.39%), and α-pinene (11.29%). BCO exhibited a moderate cytotoxicity profile indicated by IC50, which was >200 μg/mL in both cell lines. In combination with doxorubicin, BCO did not increase the cytotoxicity of doxorubicin. Moreover, BCO induced senescence by increasing 3% of the senescent cells compared with that of the untreated cells. A combination of BCO and doxorubicin increased the senescent cells by 3%–7% compared with doxorubicin alone. Therefore, the moderate cytotoxicity of BCO could be beneficial to the application of BCO as a chemotherapeutic adjuvant which increases cancer cells senescent and consequently inhibits cell proliferation.